2007
DOI: 10.4049/jimmunol.178.8.4717
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Tlr5−/− Mice Are More Susceptible to Escherichia coli Urinary Tract Infection

Abstract: Although TLR5 regulates the innate immune response to bacterial flagellin, it is unclear whether its function is essential during in vivo murine infections. To examine this question, we challenged Tlr5−/− mice transurethrally with Escherichia coli. At 2 days postinfection, wild-type mice exhibited increased inflammation of the bladder in comparison to Tlr5−/− mice. By day 5 postinfection, Tlr5−/− mice had significantly more bacteria in the bladders and kidneys in comparison to wild-type mice and showed increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
137
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 31 publications
4
137
0
3
Order By: Relevance
“…Because TLR5 is active when flagellin is administered i.n., we assume that apical/luminal signalling induces the epithelial response, as described previously [37]. It has been suggested that this type of epithelial innate mechanism is essential in mucosal defense against L. pneumophila, Pseudomonas aeruginosa and uropathogenic Escherichia coli [22,26,38]. Furthermore, respiratory pathogens that reach the basolateral side of the epithelial barrier via specific transport mechanisms or following trauma can stimulate either epithelial cells, airway smooth muscle, endothelial cells or any TLR5-expressing haematopoietic cells (such as lung macrophages and dendritic cells).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Because TLR5 is active when flagellin is administered i.n., we assume that apical/luminal signalling induces the epithelial response, as described previously [37]. It has been suggested that this type of epithelial innate mechanism is essential in mucosal defense against L. pneumophila, Pseudomonas aeruginosa and uropathogenic Escherichia coli [22,26,38]. Furthermore, respiratory pathogens that reach the basolateral side of the epithelial barrier via specific transport mechanisms or following trauma can stimulate either epithelial cells, airway smooth muscle, endothelial cells or any TLR5-expressing haematopoietic cells (such as lung macrophages and dendritic cells).…”
mentioning
confidence: 70%
“…A common stop codon polymorphism in TLR5 is associated to both increased susceptibility to pneumonia caused by the flagellated bacteria Legionella pneumophila and resistance to Crohn's disease, indicating that TLR5 signalling is relevant for mucosal immunity [20,21]. With TLR5-deficient mice, the critical role of TLR5 in mucosal inflammatory responses was established because deletion of Tlr5 gene alters response to respiratory, intestinal and urinary tract infections as well as mucosal homeostasis [1,[22][23][24][25][26]. Parenchyma and haematopoietic cells play a different role in TLR5-dependent mucosal immunity depending on the tissue studied.…”
mentioning
confidence: 99%
“…Further research into the innate immune response may elucidate pathological mechanisms underlying infectious morbidities such as tubal infertility and preterm labour, but as yet few studies have examined the functional effects of innate immune components such as NAPs and TLRs in the reproductive tract. While existing SLPI (Ashcroft et al 2000) and TLRnull (Sugawara et al 2003, Andersen-Nissen et al 2007) mutant mouse models show impaired wound healing and altered responses to infection, they have provided little information relating directly to the reproductive tract. In addition, fundamental differences in key physiological reproductive processes, such as implantation and placentation, exist between mouse and human limiting the relevance of these rodent models.…”
Section: Resultsmentioning
confidence: 99%
“…In others, such as Salmonella enterica serovar Typhimurium, fliC is expressed during invasion through Peyer's Patches but not in the mesenteric lymph nodes or spleen to promote escape from immune responses and to spread to systemic sites of replication (10). Because much attention has been focused on immune recognition of bacterial flagellin via Toll-like receptor 5 (11)(12)(13), and it is unknown how flagella contribute to ascending infections, it would be advantageous to assess the spatial and temporal expression of UPEC flagellin in real time during UTI. Noninvasive biophotonic imaging has been used for real-time monitoring of organism density and spread in various animal models of infection, including UTI caused by Pseudomonas aeruginosa and Proteus mirabilis (14)(15)(16).…”
mentioning
confidence: 99%